Scientific and Technological Mapping of the Use of Glycerin and Soapstock as Enhanced Oil Recovery Fluid - Amorim, Maria Gabriela Sena (2022)
Large amounts of oil are trapped in the wells after primary extraction. To solve this problem, advanced oil extraction methods were developed. The present study mapped the use of glycerin and soapstock, biodiesel by-products, as injection fluids to increase the recovery factor of mature wells. Questel Orbit was the database used in prospecting, where combinations of key words with international classification codes were used associated with the use of surfactants as EOR fluids, in particular crude glycerin and soapstock. The search for articles was carried out using the advanced search for keywords on the Elsevier platform. The results were thirty-one patentes and 107 articles related, where observed a diffusion of Technologies from 2015 and trends in development in China, the United States and Brazil. Greater dissemination of the theme was noted in countries that are major oil and biodiesel producers, in addition to observing the need for greater investments in the area, in order to provide economic, social and sustainable development.